Ultrafast Dynamics in Molecules, Nanostructures and Interfaces : Selected Lectures Presented at Symposium on Ultrafast Dynamics of the 7th International Conference on Materials for Advanced Technologies, Singapore, 30 June-5 July 2013 - Gurzadi͡an, G. G. (Gagik Grigorʹevich), 1957- (Series in optics and photonics, 2014)
Primary events in natural systems or devices occur on extremely short time scales, and yet determine in many cases the final performance or output. For this reason research in ultrafast science is of primary importance and impact in both fundamental research as well as its applications. This book reviews the advances in the field, addressing timely and open questions such as the role of quantum coherence in biology, the role of excess energy in electron injection at photovoltaic interfaces or the dynamics in quantum confined structures (e.g. multi carrier generation). The approach is that of a monograph, with a broad tutorial introduction and an overview of the recent results. This volume includes selected lectures presented at Symposium on Ultrafast Dynamics of the 7th International Conference on Materials for Advanced Technologies.